The Urgency of Case Method in Geography Learning - Asep Asep (JPG (Jurnal Pendidikan Geografi), 2023)
The process of organizing education through classroom learning in the current era, especially in describing learning in the era of the independent curriculum, is increasingly showing its existence. Because with this development is tucked away the purpose of the development of learning through increased competence, flexibility and character. This research aims to describe the use of case method in geography learning. This is based on the demand for students to be able to not only understand geography material, but how learning content is considered to be analyzed using cases as described in the purpose of using the case method itself. From the results of the researcher's search using the documentation method to several references, it shows that according to the characteristics of geography learning is a learning perspective (approach), tools, as well as knowledge and skills. Therefore, to understand the character and more meaningful geography learning material, the author assumes that the case method is the right approach to understanding and giving meaning to each geography content that is learned